Ethnopolitical discourse among ordinary Malaysians: the discursive constructions of unity and difference - Hashim, A. (SAGE Publications (UK and US), 2009)
A focus group of ethnically diverse Malaysians was assembled to discuss the state of multiculturalism in Malaysia. Discursive analysis was used to get at the participants’ speech practices and constructions of multiculturalism. Participants’ accounts revealed an increased social distance between the Malays and non-Malays, but differing explanations or solutions for such group boundaries. Participants’ accounts drew on various voices in representing or evaluating the current situation and how it became this way. Religion, especially Islam, was used as an ethnopolitical discourse and was articulated in different ways. For instance, the Malays invoked being Muslim as the primary source of identity and imagined community, while the non-Malays cited the politicalization of Islam as a primary cause for the increasing boundary between groups. The discussion pointed to increasing differences between Malays and non-Malays suggesting that the problem of multiculturalism has been transformed into a bi-modal ethnopolitical tension.